Food sharing with friends and acquaintances: A study in preschool boys and girls - Hallers-Haalboom, Elizabeth T.; Vermande, Marjolijn M.; van Leeuwen, Edwin J. C.; Sterck, Elisabeth H. M. (Frontiers in Psychology, 2023)
The current study examined whether preschoolers in a (semi-)natural situation shared more food with friends or acquaintances, and whether this was different between boys and girls, older and younger children, and for preferred and non-preferred food. In order to do so, we replicated and extended the classical work of Birch and Billman (1986) in a Dutch sample. Participants included 91 children aged between 3 to 6 years (52.7% boys, 93.4% Western European) from a middle- to upper-middle-class neighborhood in the Netherlands. Results revealed that children shared more non-preferred than preferred food with others. Girls gave more non-preferred food to acquaintances than to friends, whereas boys gave more to friends than to acquaintances. No effect of relationship was found for preferred food. Older children shared more food than younger children. Compared to acquaintances, friends made more active attempts to get food. Moreover, children who were not shared with were just as likely to share food as children who were shared with. Overall, only a small degree of agreement with the original study was found: Some significant findings could not be replicated, and some unconfirmed hypotheses of the original study were supported. The results underscore both the need for replications and studying the effect of social-contextual factors in natural settings.